Effects of artificial aeration, macrophyte species, and loading rate on removal efficiency in constructed wetland mesocosms treating fish farm wastewater. Issue 4 (1st July 2007) - Maltais-Landry, Gabriel; Chazarenc, Florent; Comeau, Yves; Troesch, Stéphane; Brisson, Jacques
Abstract : We studied the contribution of artificial aeration, loading rate, and macrophyte species on pollutant removal in horizontal subsurface flow constructed wetlands (HSSFCWs) treating reconstituted trout farm wastewater. Twelve 1 m 2 mesocosms located in a controlled greenhouse environment were used to test two species of macrophytes ( Phragmites australis, Typha angustifolia ), three loading rates (30, 60, and 90 L·m –2 ·d –1 ), and presence or absence of artificial aeration at the intermediate loading rate. There was no effect of any variable (macrophytes, loading, aeration) on total suspended solids (TSS) or chemical oxygen demand (COD) removal. Artificial aeration improved nitrogen removal while higher loading rates diminished removal of nitrogen and phosphorus. Macrophytes improved nitrogen and phosphorus removal, but this effect varied depending on loading rates and presence or absence of artificial aeration. We found no differences between Phragmites and Typha for treatment of trout fish farm wastewater. Under summer conditions, our results suggest that artificial aeration could be used to improve nitrogen removal by HSSFCWs. Key words: horizontal subsurface flow constructed wetlands, artificial aeration, loading rates, Phragmites australis, Typha angustifolia, fish farm wastewater.